Konstruksi, Kontestasi, Fragmentasi, dan Pluralisasi Otoritas Keagamaan Indonesia Kontemporer - Anggi Afriansyah (Studia Islamika, 2021)
Noorshahril Saat and Ahmad Najib Burhani (eds). 2020. The New Santri: Challenges to Traditional Religious Authority in Indonesia. Singapore: ISEAS Yusuf Ishak Institute.After the New Order, religious movements become increasingly popular both offline and online. The internet has become a medium for disseminating ideas and practices of religious patterns that are different from traditional religious authorities. On the other hand, there are increasing opportunities for transnational religious movements seeking to build their influence in Indonesia. Another interesting phenomenon is the presence of New Santri coming to color the world of da’wah in Indonesia through new media. Through this book, the authors try to explain the phenomena that are happening in the struggles for religious authority in Indonesia. This book describes at least three factors that significantly influence recent religious competitions, namely: globalization, post-Reformation democratization (after 1998), and the growth of various private television channels and social media users. These three factors have a strong impact in shaping and internalizing the construction, contestation, fragmentation, and pluralization of contemporary Indonesian religious authorities.